The WTO TRIPS decision on COVID-19 vaccines: What is needed to implement it? - Carlos María Correa; Nirmalya Syam (South Centre, 2022)
The 12th WTO Ministerial Conference adopted a Ministerial Decision on the TRIPS Agreement on 17 June 2022. This partially concluded almost two years of protracted discussions in response to a proposal by India and South Africa for a waiver from certain obligations under the TRIPS Agreement for health products and technologies for the prevention, treatment and containment of COVID-19. The adopted Decision only waives the obligation under article 31 (f) of the TRIPS Agreement. Developing country WTO members are now allowed to export any proportion of vaccines, including ingredients and processes, necessary for the COVID-19 pandemic that are manufactured under a compulsory license or government use authorization to other developing countries. It also contains some clarifications of relevant TRIPS provisions, while introducing a number of conditionalities that are not present in the TRIPS Agreement. This paper examines the object and scope of the Decision, the requirements established for its use, and the required actions to be taken by WTO members to implement it.
Keywords: 300; Compulsory Licenses; COVID-19; Diagnostics; Dispute Settlement; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Government Use; MC12; Pandemic; Parallel Importation; Test Data; Therapeutics; TRIPS; TRIPS Agreement; TRIPS Flexibilities; TRIPS Waiver; Vaccines; Voluntary License; World Trade Organization (WTO); WTO TRIPS Decision on COVID-19 Vaccines